The Social Optimum in the presence of Monopoly and Taxation - Green, H. A. John (Review of Economic Studies, 1961)
Journal Article The Social Optimum in the presence of Monopoly and Taxation Get access H. A. John Green H. A. John Green Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 1, October 1961, Pages 66–78, https://doi.org/10.2307/2296184 Published: 01 October 1961